Integrative multi-omics reveals a regulatory and exhausted T-cell landscape in CLL and identifies galectin-9 as an immunotherapy target - Llaó Cid, Laura; Wong, J. K. L.; Fernandez Botana, I.; Paul, Yashna; Wierz, M.; Pilger, Liesa-Marie; Floerchinger, Alessia; Tan, Chin Leng; Gonder, S.; Pagano, G.; Chazotte, Margot; Bestak, Kresimir; et al. (Nature Communications, 2025)
T-cell exhaustion contributes to immunotherapy failure in chronic lymphocytic leukemia (CLL). Here, we analyze T cells from CLL patients’ blood, bone marrow, and lymph nodes, as well as from a CLL mouse model, using single-cell RNA sequencing, mass cytometry, and tissue imaging. T cells in CLL lymph nodes show the most distinct profiles, with accumulation of regulatory T cells and CD8+ T cells in various exhaustion states, including precursor (TPEX) and terminally exhausted (TEX) cells. Integration of T-cell receptor sequencing data and use of the predicTCR classifier suggest an enrichment of CLL-reactive T cells in lymph nodes. Interactome studies reveal potential immunotherapy targets, notably galectin-9, a TIM3 ligand. Inhibiting galectin-9 in mice reduces disease progression and TIM3+ T cells. Galectin-9 expression also correlates with worse survival in CLL and other cancers, suggesting its role in immune evasion and potential as a therapeutic target.
Online veröffentlicht: 07. August 2025
Gesehen am 21.01.2026